Rivers : a very short introduction - Middleton, Nick. (New York : Oxford University Press, 2012)
Rivers have acted as cradles for civilization and agents of disaster; a river may be a barrier or a highway, bearing trade and sediment, culture and conflict. This volume is a celebration of rivers in all their diversity. The author, a geographer covers a wide and eclectic range of river-based themes, from physical geography and mythology, to industrial history and literary criticism. Offering a truly global look at rivers including the Amazon, the Ganges, the Danube, and the Mississippi, with examples from all continents, including Egypt, India, and Bangladesh, he considers the role that rivers have played in human history from settlements and trade to warfare, and also looks at the human impact upon rivers by the construction of dams and cutting of channels.
Nature's driver -- Sacred flows -- Liquid histories -- Roads that move -- Tamed rivers.
Includes bibliographical references (p. 119-121) and index.
Keywords: Rivers; Rivers in art; Rivers in literature; Rivers -- Religious aspects; Rivers -- Social aspects